Evento estético em Gianni Vattimo: a arquitetura da ontologia da atualidade - Omar Lucas Perrout Fortes de Sales (2017)
The debole philosophy from Gianni Vattimo assumes positively the nihilism on make visible the conscious thinking from its limits and takes carefully the fate of weakening of the objective and normative values from metaphysics. This work explores the thesis that the roots of the pensiero debole meet place in the Vattimos esthetic reflection. To recognize this nexus allow us to situate the protagonism from the ontological esthetic beside the philosophical hermeneutics developed by the philosopher as the ontology of actuality. The arrangement initially established between esthetics, ontology and hermeneutics goes through and engenders the posterior production from Vattimo and articulates, as it proposes, with the esthetic event privileged way to interpret the thinking from the author. Lastly, its explicated the esthetic and political development brought afloat by the ontology of actuality to translate de practical character open by the esthetic event and to compose the philosophy committed with the concrete demands from the historical subject and with the problems of your time.